The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/jbmr.1617
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-five years of PTHrP progress: From cancer hormone to multifunctional cytokine

Abstract: Twenty-five years ago a ‘new’ protein was identified from cancers that caused hypercalcemia. It was credited for its ability to mimic parathyroid hormone, and hence was termed parathyroid hormone-related protein (PTHrP). Today it is recognized for its widespread distribution, its endocrine, paracrine, and intracrine modes of action driving numerous physiologic and pathologic conditions with a central role in organogenesis. The multiple biological activities within a complex molecule with paracrine modulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
128
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(139 citation statements)
references
References 123 publications
0
128
1
3
Order By: Relevance
“…The advantage of the novel ephrin mechanism is that it prevents resorption from competing with synthesis at the same physical location on remodeling bone surfaces. These authors' hypothesis is supported by molecular profiling studies by Allan et al that found ephrin-B2 expression was increased in OBs and osteoblastic cell lines in response to treatment with parathyroid hormone (PTH) or parathyroid hormone-related peptide (PTHrP), both of which are important regulators of bone homeostasis (Silva et al, 2011;McCauley and Martin, 2012).…”
Section: Introductionmentioning
confidence: 91%
“…The advantage of the novel ephrin mechanism is that it prevents resorption from competing with synthesis at the same physical location on remodeling bone surfaces. These authors' hypothesis is supported by molecular profiling studies by Allan et al that found ephrin-B2 expression was increased in OBs and osteoblastic cell lines in response to treatment with parathyroid hormone (PTH) or parathyroid hormone-related peptide (PTHrP), both of which are important regulators of bone homeostasis (Silva et al, 2011;McCauley and Martin, 2012).…”
Section: Introductionmentioning
confidence: 91%
“…The factor, which had long been suspected of being a PTH-like entity, was indeed found to be a polypeptide that not only induced the same effects on bone and kidney cells as PTH did, but shared amino acid sequence homology with PTH, at least within the N-terminal region that was known to be critical for activity ( Fig. 2) (Suva et al, 1987;Nissenson et al, 1988;McCauley and Martin, 2012). A true biologic role for PTHrP was then established in 1994 by the gene "knockout" approach, because the PTHrP-null mice died at birth with developmental abnormalities, particularly affecting the skeleton (Karaplis et al, 1994).…”
Section: B Parathyroid Hormone-related Proteinmentioning
confidence: 97%
“…PTHrP was thus found to be produced by cells at the peripheries of the developing bone template and to act in a paracrine fashion on the chondrocytes within the template to promote their proliferation and slow their terminal differentiation toward the hypertrophic state (Kronenberg, 2006). It is now clear that in addition to bone, PTHrP plays a role in the development of several other tissues, including the mammary glands (Wysolmerski et al, 1998) and teeth , and is widely expressed among various organ systems, suggesting a generally broad functional role as a paracrine-acting regulatory factor (Trivett et al, 2005;McCauley and Martin, 2012).…”
Section: B Parathyroid Hormone-related Proteinmentioning
confidence: 99%
“…(2,3) PTHrP is a polyhormone that can be translated and processed into several smaller bioactive forms. The N-terminal region of PTHrP, ie, PTHrP , mediates "classical" PTH-like effects.…”
mentioning
confidence: 99%